The Concept of Al-Thawābit and Al-Mutaghayyirāt in Technological Innovation According to Maqāṣid al-Sharīʿah - Harun, Muhammad Safwan; Abdullah, Luqman; Harith Idris, Muhammad Ammar; Meerangani, Khairul Azhar; Ali, Abdul Karim (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2025)
The rapid advancement of modern technology, particularly in the context of the Fourth Industrial Revolution (IR 4.0), presents Muslims with a range of complex challenges, including ethical dilemmas and questions regarding the social impact of innovations such as artificial intelligence, biotechnology and digital media. These challenges are significant as they impact daily life and raise profound concerns about the preservation of religious values, identity and social order. While technological progress offers undeniable benefits, it also generates indirect risks that may be overlooked if assessed solely from a utilitarian or secular perspective. Against this backdrop, Islamic law, guided by the higher objectives of maqāṣid al-sharī`ah provides a principled and comprehensive framework for evaluating technological innovation, ensuring that developments remain aligned with core Islamic moral and ethical standards and ultimately promote human well-being in a holistic sense. Central to this approach are the concepts of al-thawābit (the immutable) and al-mutaghayyirāt (the changeable) which serve as critical tools for adapting Islamic legal rulings to new technological realities. This article adopts a library research and content analysis methodology to examine existing literature and provide a comprehensive understanding of Shariah’s role, specifically through the lens of maqāṣid al-sharī`ah in regulating technological advancements. The study concludes that although technology constitutes part of al-mutaghayyirāt and continues to evolve, the immutable principles of maqāṣid al-sharī`ah serve as an essential safeguard to ensure that technological change continues to advance the holistic well-being of humanity. In sum, the maqāṣid al-sharī`ah framework provides the critical criteria for balancing benefits and harms, ensuring that technological advancement ultimately serves the comprehensive well-being and public interest (maṣlaḥah) of humanity.